Orenburg State University as an Agent of Regional Development - Zh. A. Ermakova (Высшее образование в России)
The article presents the analysis of Orenburg State University multifunctional activity in the context of solving tasks of socio-economic and technological development of the region. Strategic tasks of University’s activities in the regional context include the development of the territory, enhancing the quality of life, development of the advanced technologies, both technical and social, development of human resources. Educational and research activities of the University provide personnel and technological support of the priority areas of Orenburg region development. key aspects of personnel and innovation-technological support of the Orenburg region development trends are indicated, such as machine building, construction, biotechnology, IT, nanotechnology, power saving, tourism. The issues of education, science and industry integration as well as international cooperation development are highlighted. The article dwells on the realization of the “university’s third mission”, its societal duties and contribution to the development of the region.